Control System Performance Analysis of Boiler’s Main Parameters in Steam Power Plant - Agus Yogianto, Tri Wahyu O Putri , Septianissa Azzahra (International Journal of Advanced Science and Technology, 2020)
Steam Power Plant has been implementing the usage of non-oil fuel (natural gases) as its fuel. Like another general energy conversion machines, the efficiency aspect becomes the priority, thus it needs a control system that is able to control the energy conversion process optimally. The efficient boiler performance is determined by optimal control system in its boiler system. Therefore, in this study discusses the performance of boiler main parameters that associated with the boiler control system at Steam Power Plant PT. PJB UP Muara Karang. This research was done by observing the main parameters of boiler then analysing those parameters based on its variance and error value. From the analysis, the parameter that has the largest variance is furnace pressure, which is around 21. A quite large variance in loop furnace pressure because the combustion chamber pressure does not have setpoint, so it is very dependent on the dynamics that occur in the combustion chamber itself. While the errors of the main parameters have relatively small errors below the 2% limit. In general, it can be said that the performance of the main parameters of the boiler as a result of the work of the control system shows good performance.